An evaluation of electrochemical performance of a solid oxide electrolyzer cell as a function of co-sintered YSZ-SDC bilayer electrolyte thickness. (15th October 2017) - Heidari, Dorna; Javadpour, Sirus; Chan, Siew Hwa
Graphical abstract: Highlights: Effect of YSZ-SDC bilayer electrolyte on SOEC electrochemical performance. Effects of the performance of YSZ blocking layer thickness, fuel humidity, and temperature. Successful use of YSZ blocking layer on the SDC electrolyte to form the YSZ-SDC bilayer electrolyte. Abstract: Using porous Ni-YSZ (Yttria Stabilized Zirconia, ZrO2 -Y2 O3 ) as a fuel electrode, dense YSZ-SDC (Samaria Doped Ceria, Sm0.2 Ce0.8 O1.9 ) as an electrolyte, and porous 20 wt%SDC-80 wt% BSCF (Ba0.5 Sr0.5 Co0.8 Fe0.2 O3−δ ) as an air electrode, with the three distinguishable layers well adhered to each other, a Ni-YSZ/YSZ-SDC/BSCF-SDC solid oxide electrolyzer cell (SOEC) was constructed in order to satisfy the aim of this research which is studying the effect of YSZ blocking layer on its electrochemical performance over the temperature range of 650–800 °C. Coating of SDC with a very thin layer of YSZ to form a YSZ-SDC bilayer electrolyte was performed using the spin coating technique in order to prevent the open circuit voltage (OCV) loss and enhance the chemical stability of doped ceria electrolyte in reducing atmospheres. For further examination to find out which microstructure is crack-free in order to provide electrical current leakage prevention in the SDC layer and at the same time to have an optimum thickness, impedance measurement under 0.1 V bias with different hydrogen humidity level as well as cell polarization study were conducted at 800 °C. Detailed investigations on the microstructural, electrochemical, and power measurement data confirmed that a bilayer electrolyte structure with 3.5 µm YSZ thickness can provide chemical, mechanical, and structural stability of the YSZ-SDC bilayer electrolyte in the Ni-YSZ/YSZ-SDC/BSCF-SDC single cell.